Ten popes who shook the world - Duffy, Eamon (Yale University Press, 2011)
The Bishops of Rome have been Christianity's most powerful leaders for nearly two millennia, and their influence has extended far beyond the purely spiritual. The popes have played a central role in thehistory of Europe and the wider world, not only shouldering the spiritual burdens of their ancient office, but also in contending with- and sometimes precipitating- the cultural and political crises of their times. In an acclaimed series of BBC radio broadcasts Eamon Duffy explored the impact of ten popes he judged to be among 'the most influential in history'. With this book, readers may now also enjoy Duffy's portraits of ten exceptional men who shook the world. The book begins with St Peter, the Rock upon whom the Catholic Church was built, and follows with Leo the Great (fifth century), Gregory the Great (sixth century), Gregory VII (eleventh century), Innocent III (thirteenth century), Paul III (sixteenth century), and Pius IX (nineteenth century). Among twentieth-century popes, Duffy examines the lives and contributions of Pius XII, who was elected on the eve of the Second World War, the kindly John XXIII, who captured the world's imagination, and John Paul II, the first non-Italian pope in 450 years. Each of these ten extraordinary individuals, Duffy shows, shaped their own worlds, and in the process, helped to create ours.